The time of ecological rights - Guedes, Marcio Bulgarelli; Ramos , Paula Gabriela Coetti; Penna, Maria Cristina Vitoriano Martines; Guedes, Laise Reis Silva; Lehfeld, Lucas de Souza (Seven Editora, 2024)
The article analyzes the metamorphosis of law to the end of the promotion of ecological rights. It takes as a hypothesis whether the promises of the social contract have been fulfilled in relation to the collective good of the environment in the face of the transformations of law, society and the State in modernity. To this end, first, by linking the memories of the past, the axes of individual (or private) law and the successive solutions adopted until the contemplation of collective rights in the 1988 Constitution, with the solution of global, local and radiated collective conflicts, will be rescued; second, by turning off the past to connect the future, the standardization of ecological rights in a constitutional text will give us the opportunity to list environmental principles and outline the distribution of administrative and legislative competences in environmental matters; and, thirdly, by zooming in on the main general environmental laws, confirm that the law is transformed and that it can offer means for the recovery of the environmental deficit, according to the rural environmental registry (CAR), the environmental recovery program (PRA), the protected territorial spaces, the administrative licenses, etc., with the possibility of three-dimensional responsibility of the polluter. In conclusion, we want to confirm the hypothesis of the problem of the metamorphosis of the law and its virtuous image in front of the social mirror with the commitment to preserve and protect the environment. Finally, guided by the hypothetical-deductive method, the article makes an evaluative approach to the formal sources of the environment, based on books, scientific articles, public hearings, jurisprudence and legislation. DOI:https://doi.org/10.56238/sevened2024.026-064